1980
DOI: 10.2466/pr0.1980.46.3.831
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback and Control of Skin Cell Proliferation in Psoriasis

Abstract: The present study was designed to determine the effect of skin-temperature-biofeedback training on cellular proliferation in three psoriasis patients. It was hypothesized that (a) psoriasis patients would be able to consciously decrease skin temperature of psoriatic tissue, and (b) there would be a positive correlation between rate of cellular proliferation and temperature change.Results obtained indicated biofeedback training to be effective in decreasing the surface temperature of psoriatic tissue.A 2 X 7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several studies [70,71] have reported that temperature biofeedback training was associated with a significant decrease in the severity of psoriasis. The efficacy of this method appears to be related…”
Section: Cutaneous Blood Flowmentioning
confidence: 99%
“…Several studies [70,71] have reported that temperature biofeedback training was associated with a significant decrease in the severity of psoriasis. The efficacy of this method appears to be related…”
Section: Cutaneous Blood Flowmentioning
confidence: 99%
“…Benoit and Harrell demonstrated that biofeedback training was effective in enabling subjects with severe psoriasis to decrease voluntarily the surface temperature of psoriatic tissue. 8 They also showed that the cell-turnover rate decreased in biopsies from pretraining to posttraining, although statistical analysis was not done due to the small number of participants (N = 3). Two subjects showed considerable clinical improvement and one subject showed slight improvement in all psoriatic plaques, with improvements still evident at 4-month follow-up.…”
Section: Biofeedbackmentioning
confidence: 99%